Diseño y propuesta de un sistema de aislamiento térmico en paredes residenciales a base de lana de oveja - Ortiz Villegas, Lenin Geovanny (2018)
In the present project a thermal insulator is proposed using a natural product such as sheep wool, this material will have the purpose of improving the temperature inside a house and in this way making the stay of its inhabitants more comfortable, also it will be able to fight the low temperatures in the mountain region mainly in the one in Machachi, cantonal head of the Canton Mejía where this work is focused. The objective of this project, based on the aforementioned considerations, is to contribute to the well-being of the people living in this area, counteracting the cold climate that sometimes surrounds the area, with thermal insulation based on a natural product. In Ecuador there are some products that are used as thermal insulation, among the best known are: expanded polystyrene and rock wool. These two materials are characterized by their thermal properties, the first based on plastic grains and the second based on volcanic rock, which are more common use but have health risks due to their small particles that can be inhaled or can splash to the eyes or skin when making cuts or when installing, also need to go through a bake at high temperatures while natural sheep wool does not require this procedure and does not pose health risks as it is one hundred percent natural and free of particles that can affect the health of people also highlighting that it is a renewable product.